The Many Faces of Elongator in Neurodevelopment and Disease - Kojic, Marija; Wainwright, Brandon (Frontiers in Molecular Neuroscience, 2016)
Development of the nervous system requires a variety of cellular activities, such as proliferation, migration, axonal outgrowth and guidance and synapse formation during the differentiation of neural precursors into mature neurons. Malfunction of these highly regulated and coordinated events results in various neurological diseases. The Elongator complex is a multi-subunit complex highly conserved in eukaryotes whose function has been implicated in the majority of cellular activities underlying neurodevelopment. These activities include cell motility, actin cytoskeleton organization, exocytosis, polarized secretion, intracellular trafficking, and the maintenance of neural function. Several studies have associated mutations in Elongator subunits with the neurological disorders familial dysautonomia, intellectual disability, amyotrophic lateral sclerosis and rolandic epilepsy. Here, we review the various cellular activities assigned to this complex and discuss the implications for neural development and disease. Further research in this area has the potential to generate new diagnostic tools, better prevention strategies and more effective treatment options for a wide variety of neurological disorders.